Identifikasi Faktor-faktor Internal dan Eksternal Pada Usaha Keripik Singkong Industri Rumah Tangga di Desa Tulaan Kecamatan Gunung Meriah Kabupaten Aceh Singkil (Studi kasus Pada Indutri Rumah Tangga Cap Murti) - Vira Afriliyandha; Mustafa Usman; T. Saiful Bahri (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
The household cassava chips industry, Cap Murti, produces cassava chips and can become the main industry in Tulaan Village, Gunung Meriah District, Aceh Singkil Regency. One of them is product development. Good product development requires proper marketing to achieve the goals and desires of the domestic industry so that Cap Murti's domestic industry can continue to grow. According to (Saparudin, 2008), the growth and development of the domestic industry in each period has an impact on increasing competition. The increasingly fierce competition tends to balance the level of profit. The purpose of this study was to determine the factors that influence the development of cassava chips business in the home industry of Cap Murti in Tulaan village, Gunung Meriah district, Aceh Singkil district. This research consists of descriptive analysis of data and analysis of strategic planning in the form of tables, charts and descriptions. Based on the results of the study, it was found that the internal factors that could affect the Cap Murti Home Industry business in the form of strength factors were as follows (taking advantage of opportunities), namely: Internal factors consisted of: 1) Availability of raw materials; 2) Products are easily absorbed by the market; 3) Products are made continuously; 4) Products are easy to produce; 5) Durable product. External factors consist of: 1) Lack of working capital; 2) Equipment is still simple; 3) Promotion is still lacking; 4) Product packaging is less attractive; 5) Limited production capacity. Meanwhile, external factors that affect Cap Murti's home industry business consist of: 1) Increasing market demand; 2) Establishment of good communication between customers and the company; 3) Cassava chips fans come from all walks of life; 4) New customers; 5) The taste of the product that has a characteristic. While the threat factors consist of: 1) The increase in the price of raw materials; 2) The emergence of competitors for similar products and other products; 3) The decline in people's purchasing power due to inflation; 4) It is difficult to get a qualified workforce because of small capital; 5) Weak in market competition due to simple technology. Cap Murti's home industry business strategy based on the results of the SWOT analysis is in quadrant I, which means aggressive strategy (SO) or using strengths and taking advantage of opportunities.